Recovery interventions and strategies for improved tennis performance - Kovacs, M. S.; Baker, L. B. (British Journal of Sports Medicine, 2014)
Improving the recovery capabilities of the tennis athlete is receiving more emphasis in the research communities, and also by practitioners (coaches, physical trainers, tennis performance specialists, physical therapists, etc). The purpose of this article was to review areas of recovery to limit the severity of fatigue and/or speed recovery from fatigue. This review will cover four broad recovery techniques commonly used in tennis with the belief that the interventions may improve athlete recovery and therefore improve adaptation and future performance. The four areas covered are: (1) temperature-based interventions, (2) compressive clothing, (3) electronic interventions and (4) nutritional interventions.